The application of a method of walking galery students to promote entrepreneurship - Hamid, Abdurahman (Pinisi Business Administration Review, 2025)
The objective of this investigation is to elucidate the process of utilizing the Walking Gallery method to cultivate entrepreneurial qualities. There is still a need for development in the implementation of an entrepreneurial spirit or character, particularly in the learning process. This research focuses on qualitative descriptive analysis with subjects purposively recruited from groups of students enrolled in entrepreneurship courses. Sixteen students from the Mathematics Education Study Program at the Faculty of Mathematics and Natural Sciences, Makassar State University participated in research during the even semester of the 2024/2025 academic year. Data acquired by observational methodology. The research findings were qualitatively examined, revealing that the Walking Gallery technique enhances students' entrepreneurial spirit. The Walking Gallery technique helps students develop entrepreneurial qualities including commitment, optimism, self-assurance, and the capacity to spot opportunities. The utilization of these characters has been delineated in a publication at an entrepreneurial exhibition.